Literasi Keuangan Untuk Generasi Muda Milenial Bagi Siswa SMKN 2 Sampang - Ahmad Wahyudin; Faisol Faisol; Zulviar Anas (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Students at SMK 2 Sampang are a millennial generation that has great potential and productivity but lacks understanding regarding understanding financial literacy. Many of this generation are currently very consumptive, not very sensitive to the environment, do not understand priorities, and rarely understand the correct functions of finance. With this solution, it is hoped that it can overcome the problems faced by students at SMK 2 Sampang, especially regarding financial literacy skills among millennials, who of course are of productive age who will provide performance to our country. The method used in this service uses direct lectures, presentations using Power Point and question and answer sessions. From this activity, all students at SMKN 2 Sampang already understand the importance of financial literacy.